2010
DOI: 10.1007/s12230-010-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Potato Mop-Top Virus in Soil Using Bait Plant Bioassay and RT-PCR-microplate Hybridization

Abstract: Spraing (brown rings or arcs) of potato caused by Potato mop-top virus (PMTV) occurred in a field of Tokachi, Hokkaido, Japan in 2005. To monitor the expansion of spraing-affected areas, we developed a soil diagnostic method that consisted of a bioassay using tomato as bait plant to trap the vector of PMTV, Spongospora subterranea, the causal agent of powdery scab of potatoes, followed by reverse transcription-polymerase chain reaction-microplate hybridization (RT-PCR-MPH) to detect the virus from roots of bai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Double‐antibody sandwich enzyme‐linked immunosorbent assay (DAS‐ELISA), immunocapture reverse transcription polymerase chain reaction (IC‐RT‐PCR) using PMTV coat protein (CP)‐specific polyclonal or monoclonal antibodies and virus‐specific primers (Sokmen et al , 1998; Sandgren et al , 2001; Germundsson et al , 2002; Latvala‐Kilby et al , 2009), RT‐PCR, or real‐time RT‐PCR using CP ‐specific primers (see below) are all suitable methods for PMTV detection. Furthermore, other RT‐PCR‐based methods such as qualitative amplification‐based specific hybridisation (FLASH‐PCR) (Ryazantsev & Zavriev, 2009) and RT‐PCR‐microplate hybridisation (Nakayama et al , 2010) have been applied to detect PMTV.…”
Section: Reliable Means To Detect Potato Mop‐top Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Double‐antibody sandwich enzyme‐linked immunosorbent assay (DAS‐ELISA), immunocapture reverse transcription polymerase chain reaction (IC‐RT‐PCR) using PMTV coat protein (CP)‐specific polyclonal or monoclonal antibodies and virus‐specific primers (Sokmen et al , 1998; Sandgren et al , 2001; Germundsson et al , 2002; Latvala‐Kilby et al , 2009), RT‐PCR, or real‐time RT‐PCR using CP ‐specific primers (see below) are all suitable methods for PMTV detection. Furthermore, other RT‐PCR‐based methods such as qualitative amplification‐based specific hybridisation (FLASH‐PCR) (Ryazantsev & Zavriev, 2009) and RT‐PCR‐microplate hybridisation (Nakayama et al , 2010) have been applied to detect PMTV.…”
Section: Reliable Means To Detect Potato Mop‐top Virusmentioning
confidence: 99%
“…This virus has also been detected in Costa Rica in Central America (Montero‐Astúa et al , 2008) and the United States and Canada in North America (Xu et al , 2004; P. Hamm, Oregon State University, personal communication ). In Asia, PMTV occurs on Hokkaido Island in Japan (Imoto et al , 1981; Nakayama et al , 2010). In Europe, PMTV was first detected in Ireland, England and Scotland (Calvert & Harrison, 1966) and in the Netherlands (van Hoof & Rozendaal, 1969) but has not been reported in the Netherlands ever since.…”
Section: Introductionmentioning
confidence: 99%
“…Later PMTV was detected in potato tubers of England, Scotland and Ireland (Calvert and Harrison, 1966). In Asia, PMTV was detected in Hokkaido islands of Japan (Nakayama et al, 2010) and in China. PMTV has been detected from the Czech Republic and Switzerland (Schwärzel, 2002).…”
mentioning
confidence: 99%
“…Therefore, for detection of PMTV, virus-specific methods such as PMTV coat protein (CP) specific antibodies, DAS-ELISA, immune capture reverse transcription polymerase chain reaction (IC-RT-PCR) or RT-PCR using PMTV specific primers techniques are used (Sandgren et al, 2001). Modern methods such as RT-PCR micro-plates hybridization and fluorescent amplification based specific hybridization (FLASH-PCR) have also been applied to improve PMTV detection ( (Nakayama et al, 2010) Enzyme linked immunusorbent Assay (ELISA) is reported by several researchers as a best option for detection PMTV (Sokmen et al, 1998). RT-PCR having fluorescent assays have increased accuracy in diagnosis of PMTV (Mumford et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation